2013
DOI: 10.1021/am4013819
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Graphitic Carbon Nitride–Bi2WO6 Heterojunctions with Enhanced Visible Light Photocatalytic Activities

Abstract: Graphitic carbon nitride (C3N4) was hybridized by Bi2WO6 via a hydrothermal method. The high-resolution transmission electron microscopy (HR-TEM) results reveal that an intimate interface between C3N4 and Bi2WO6 forms in the heterojunctions. The UV-vis diffuse reflection spectra show that the resulting C3N4-Bi2WO6 heterojunctions possess more intensive absorption within the visible light range in comparison with pure Bi2WO6. These excellent structural and spectral properties endowed the C3N4-Bi2WO6 heterojunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
224
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(241 citation statements)
references
References 43 publications
17
224
0
Order By: Relevance
“…It was possible that with the addition of AO, holes were quenched, thus, more electrons reacted with O 2 to form ÁO 2 -instead of the rapid recombination with holes, it could effectively accelerate the photogenerated electron-hole pairs separation. This phenomenon was observed in the previous study [27,40,41]. In the Ag 2 CO 3 system, the degradation rates of RhB were inhibited when these three scavengers were added, respectively, and the inhibition performance followed the order p-BQ [ AO [ t-BuOH (Fig.…”
Section: Resultssupporting
confidence: 82%
“…It was possible that with the addition of AO, holes were quenched, thus, more electrons reacted with O 2 to form ÁO 2 -instead of the rapid recombination with holes, it could effectively accelerate the photogenerated electron-hole pairs separation. This phenomenon was observed in the previous study [27,40,41]. In the Ag 2 CO 3 system, the degradation rates of RhB were inhibited when these three scavengers were added, respectively, and the inhibition performance followed the order p-BQ [ AO [ t-BuOH (Fig.…”
Section: Resultssupporting
confidence: 82%
“…1,13 It is expressly thermal and photochemical stable owing to the high polymeric degree and p-conjugated structure and can thus undergo photocatalysis under visible light without modication.…”
Section: 7-9mentioning
confidence: 99%
“…1,20 Active species trapping and hydroxyl radical quanti-cation experiments were therefore conducted to estimate and propose the possible photocatalytic mechanism, as shown in Fig. 10.…”
Section: Proposed Photocatalytic Mechanismmentioning
confidence: 99%
“…Thus, its bandgap was much larger than that of the macroporous samples, being consistent with its UV-vis absorbance spectrum ( Figure S3 in the supplementary material 19 ). It is known that the mechanism for photocatalytic degradation of organic pollutant is closely related to the photocatalyst used, [22][23][24] in which the potential levels of band edges play a crucial role. For example, Katsumata et al used bisphenol A as the target organic pollutant and proved that the photocatalytic degradation mechanism over Ag 3 PO 4 catalyst was direct hole-oxidation.…”
mentioning
confidence: 99%
“…22 Tian et al revealed that the degradation of methyl orange over C 3 N 4 /Bi 2 WO 6 heterojunctions was primarily dependent on the oxidation of O 2 · − . 23 Bui et al demonstrated that ·OH was the main oxygen species in the photocatalytic degradation of benzene by anatase TiO 2 . 24 So far, however, few works have been reported in the photocatalytic degradation of organic pollutant, especially for the mechanistic investigation, over GaN/ZnO solid solution.…”
mentioning
confidence: 99%